Do All Switches Cost the Same? Reliability of Language Switching and Mixing Costs. Issue 1 (7th January 2021) - Segal, Dorit; Prior, Anat; Gollan, Tamar H.
The current study examined the reliability and consistency of switching and mixing costs in the language and the color-shape tasks in three pre-existing data sets, to assess whether they are equally well suited for the study of individual differences. Specifically, we considered if the language task is as reliable as the color-shape task – an important question given the wide use of language switching tasks but little information available to address this question. Switching costs had low to moderate reliability and internal consistency, and these were similar for the language and the color-shape tasks. Mixing costs were more reliable in the language task than in the color-shape task when tested twice on the same day and trended in the same direction when tested a week apart. In addition, mixing costs were larger and more consistent than switching costs in all data sets and they were also were more reliable than switching costs in the language task when tested on the same day. These results reveal the language task to be as good as the color-shape task for measuring switching and mixing ability. Low variability of switching costs may decrease their reliability and consistency, in turn interfering with the chance of detecting cross task correlations. We advocate for exploring procedures to increase the variability of switching costs, which might increase reliability and consistency of these measures, and improve the ability to determine if bilingual language use relies on cognitive mechanisms that overlap with those underlying nonlinguistic multi-tasking.